2021
DOI: 10.1002/adom.202101120
|View full text |Cite
|
Sign up to set email alerts
|

Strong Coupling of Exciton and High‐Q Mode in All‐Perovskite Metasurfaces

Abstract: Recently developed halide perovskite semiconductors are viewed as an excellent platform to realize exciton‐polariton at room temperature due to their large oscillation strength. Here, the optimized strong coupling between the exciton of perovskite and quasi‐bound state in the continuum (QBIC) with high‐quality factor (Q‐factor), supported by all‐perovskite metagrating, including magnetic dipole (MD)‐QBIC and toroidal dipole (TD)‐QBIC is demonstrated. By taking advantage of extreme electric field confinement en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 53 publications
2
18
0
Order By: Relevance
“…85 Theoretical studies on polaritonic BICs in the perovskite platform were also reported recently. 86,87 In conclusion, we demonstrated topological polarization singularities in polariton emission. The polarization vortices (in circular patterns) and CP eigenstates (in symmetry-broken patterns) were measured by the Stokes parameter measurements of PL in momentum space.…”
supporting
confidence: 50%
See 1 more Smart Citation
“…85 Theoretical studies on polaritonic BICs in the perovskite platform were also reported recently. 86,87 In conclusion, we demonstrated topological polarization singularities in polariton emission. The polarization vortices (in circular patterns) and CP eigenstates (in symmetry-broken patterns) were measured by the Stokes parameter measurements of PL in momentum space.…”
supporting
confidence: 50%
“…The Bose–Einstein condensation was demonstrated at low temperature using polariton BICs, and a polarization vortex in the perovskite metasurface was observed at room temperature . Theoretical studies on polaritonic BICs in the perovskite platform were also reported recently. , …”
mentioning
confidence: 90%
“…While most of the milestones of polaritonic physics have been achieved with excitonic materials operating at cryogenic temperatures (≈10 K), recent progress in materials science has promoted many polaritonic demonstrations at room temperature with a wide variety of high bandgap semiconductors, ranging from GaN, [24,25] ZnO, [26] to organic semiconductors, [27,28] and transition metal dichalcogenide monolayers, [29,30] as well as perovskite materials. [31][32][33][34][35][36][37][38][39][40][41] Very recently, the strong coupling regime between photonic BICs and excitonic resonances has been theoretically suggested, [42][43][44][45] with two experimental demonstrations. [46,47] The result of such a coupling is the formation of polariton-BICs (pol-BICs): hybrid excitations that are completely decoupled from the radiative continuum.…”
Section: Introductionmentioning
confidence: 99%
“…[38] Most recently, it has been theoretically suggested that perovskite metasurfaces can be harnessed to engineer the imaginary part (i.e., losses) of the polaritonic energy-momentum dispersion at room temperature via BIC and exceptional point concepts. [43,45] On the other hand, purely photonic BICs in perovskite-based resonant metasurface have been reported to make ultra-fast switches [7] and tunable microlasers. [49] In this work, we experimentally demonstrate the formation of pol-BICs in an excitonic metasurface made from hybrid 2D perovskites.…”
Section: Introductionmentioning
confidence: 99%
“…1,21 Later on, multilayer microcavity schemes with some large binding energy materials were used to obtain hybrid exciton-polariton, [22][23][24][25][26][27] but these were limited by the difficulty of fabrication. Very recently, thanks to the incorporation of lead halide perovskites [28][29][30][31][32] and two-dimensional materials, [33][34][35][36][37][38][39] the disadvantages faced previously have been swept away, which paves the way for the realization of exciton-polariton through strong coupling with specially designed photonic structures at room temperature.…”
Section: Introductionmentioning
confidence: 99%